2009
DOI: 10.1016/j.anbehav.2009.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Do adult eastern bluebird, Sialia sialis, males recognize juvenile-specific traits?

Abstract: Juveniles of many avian species possess spotted or mottled plumage that is distinct from the plumage of adults. Such plumage has typically been assumed to aid in camouflaging vulnerable immature birds. Here, we propose that spotty plumage signals juvenile status, thereby decreasing aggression from territorial adults. We tested this hypothesis by measuring the aggressive responses of adult eastern bluebird males to different combinations of simultaneously presented taxidermic mounts. We found that territorial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
1
14
1
1
Order By: Relevance
“…Following previous studies [15,16,36,37] we adopted a simultaneous presentation of dummy dyads at host nests (i.e., essentially a choice test). Great reed warblers attack almost all intruders near their nests, including the mounts of both cuckoo morphs and sparrowhawks at the highest levels of aggression [5,15,16,38-40].…”
Section: Methodsmentioning
confidence: 99%
“…Following previous studies [15,16,36,37] we adopted a simultaneous presentation of dummy dyads at host nests (i.e., essentially a choice test). Great reed warblers attack almost all intruders near their nests, including the mounts of both cuckoo morphs and sparrowhawks at the highest levels of aggression [5,15,16,38-40].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in migratory passerines, there are no juveniles in the population until the earliest broods fledge, and thus the mimetic function of dull colouration is not possible until the second breeding attempt (Schwarzová, 2010). In light of the foregoing, mimicry of juveniles is rarely invoked to explain delayed plumage maturation notwithstanding that the underlying assumption that adults display less aggression to conspecific juveniles than other conspecific adults appears to be sound (Ligon & Hill, 2009).…”
Section: (B) Assessementmentioning
confidence: 99%
“…However, the eastern bluebird is one of the few thrush species for which we have detailed information on breeding duration and territoriality, and we know that juvenile eastern bluebirds should benefit from an honest signal of age and sexual immaturity. In fact, it has recently been shown that adult males use plumage colour and pattern as cue when attacking territorial intruders and direct significantly less aggression towards models bearing juvenal plumage (Ligon and Hill 2009).…”
Section: Discussionmentioning
confidence: 99%